A Network and Repository for Online Laboratory based on Ontology - Saliah-Hassane, Hamadou (2014)
Our propose is to build a network of virtual laboratories and also use it as a global repository of online laboratory’s and experiences. This set of virtual and online laboratories can be “stored” in an “virtual closet”, and also the system will allow us to build new experiences and online laboratories, and store them is this “virtual closet”. With the drawing of this new standard we pretend define methods for storing and retrieving learning objects for remote laboratories. The objective of this standard is also define methods for linking learning objects to design and implement smart learning environments for remote online laboratories. The objects defined by this standard are, for example, interfaces for devices connected to user computers over computers networks and the devices themselves. They are also learning scenarios or collaboration tools for communications necessary to conduct an activity of practical online laboratory work, they will allow to design and implement mechanisms that make smart learning environment formed by the ad hoc aggregation of learning objects taking always into account the pedagogical context for their use. This will allow to easy design and implement the pedagogically driven remote laboratory environment and experiments as also is learning environments. The experiences and laboratories are build using the parts and separate components that we have in a separate “virtual closet” with parts, components, and already build experiences. To build this complex network we need to find a system that supports effectively this structure. This probably will be a enormous database of v-labs and independent elements, where will be possible sometimes to “recycle” some of the elements. For this structure we propose an Ontology because it allows to “re-use” the same element several times in many experiences, and provide a very detailed description of each kind of element through is classes and sub-classes.